Acupressure LI4 and SP6 on Pain with Quality of Life in Post Partum Sectio Caesarea - Azizah, Nurul; Rosyidah, Rafhani; Kusumawardani, Paramitha Amelia; Jayanti, Ratna Dwi (Universitas Islam Lamongan, 2022)
Pain is an unpleasant experience. In patients who still feel pain, it will affect the mobilization of the mother after cesarean section and all aspects of quality of life. Various attempts have been made to relieve pain both pharmacologically and non-pharmacologically. Acupressure LI4 and SP6 are believed to reduce pain. This study aims to identify the effect of Hegu LI4 and SP6 acupressure on Pain on Quality of Life in Post Partum SCThe research design used was a quasi-experimental with pre-post test non-equivalent control group design. The sampling technique was non-probabilty sampling with consecutive sampling with a total sample of 30 respondents in the treatment group and the control group. Independent bivariable analysis until T-test with a significance value of P <0.05, multivariable analysis using linear regression. The results of this study are expected to help postpartum Sectio Caesarea mothers in reducing pain. The results of this study can reduce pain and improve the quality of life for postpartum SC which will be the basis for studies in the field of obstetrics